Comparison of Non-Linear and Linear Ho Models Applied for Copper Ions Sorption on Geopolymer - Mužek, Mario Nikola (Array, 2021)
The Ho pseudo-second-order model is the best fitting model in describing the sorption of copper ions on synthesized geopolymer for the selected experimental conditions (particle size 0.071–0.090 mm at agitation speed of 240 rpm). For that reason, a comparison of one non-linear and five linear forms of the Ho pseudo-second-order model was made in the present study in order to obtain the optimum sorption kinetic parameters using the experimental kinetic data obtained for the copper ions sorption process on the synthesized geopolymer. Taking all the results into consideration, the non-linear Ho model proved to be more consistent in describing the copper ions sorption on geopolymer for various initial concentrations of sorbent, as well as for various temperatures.